(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This study explores the defensive architecture and urban development of Khorezm between the 5th and 9th centuries AD, focusing on fortresses, palaces, and defensive walls. Khorezm, a significant cultural and trade hub, played a pivotal role in shaping Central Asian architecture. However, limited comprehensive analysis exists on the construction techniques, spatial organization, and sociopolitical significance of its architectural complexes during this period. To address this gap, this research synthesizes findings from archaeological excavations documented in the Khorezm region, with emphasis on fortifications such as Sheraz Kala and Hazarasp. The study employs a multidisciplinary approach, combining architectural analysis and material culture studies to investigate construction methods, urban layouts, and defensive strategies. The findings reveal the use of mud bricks and baked bricks in fortifications, with complex layouts designed for both protection and governance. Key discoveries include multi-functional rooms, well-preserved defensive walls, and evidence of Zoroastrian burial practices within these structures. Urban centers demonstrated a strategic integration of residential and military architecture, reflecting a blend of local innovations and regional influences. The results indicate that Khorezm’s defensive architecture not only safeguarded its inhabitants but also facilitated administrative control and cultural continuity. These insights contribute to the broader understanding of Central Asian architectural history and underscore the importance of preserving Khorezm’s archaeological heritage for future research and cultural tourism. This study provides a foundation for further exploration of urban and defensive systems in ancient civilizations of the region.